Economic consequences of ecological change: restoration options for the Mfolozi floodplain and implications for Lake St. Lucia, South Africa - Collings, Sandy Lyn (Rhodes University, Faculty of Science, Department of Environmental Science, 2010)
Lake St Lucia in northern KwaZulu-Natal, South Africa, experiences severe ecological stress during dry periods largely as a result of diminishing freshwater supplies and conditions of hypersalinity. Possible intervention involves diverting the Mfolozi River to the St Lucia Lake system. However, due to high sediment loading, water from the Mfolozi river requires considerable filtration before a link can be established. A suggested option considered in this study is to restore the existing sugarcane farmlands on the Mfolozi Floodplain (~20 800 ha) to previous wetland conditions to reinstate a sediment removal function amongst other benefits. Proposed restoration will have a direct impact on the industries currently supported by the iSimangaliso Wetland Park and the Mfolozi Floodplain (tourism, sugar, conservation). to understand a measure of such impacts, ecosystem services for both Lake St Lucia and the Mfolozi Floodplain were analysed (flood alleviation, water provision, water purification, sediment regulation, tourism, fisheries, vegetation for harvest, existence, cultural and research). Annual economic values for each ecosystem service were determined by means of valuation methods that included benefit transfer and replacement cost. Results showed a current annual minimum value of the Mfolozi Floodplain and Lake St Lucia as greater than R21 million and R1.1 billion respectively. Partial restoration of the floodplain (~6 000 ha) is expected to increase the sum of all ecosystem services values by approximately 26% for the Mfolozi Floodplain and by 23% for the St Lucia System. Full restoration (~20 800 ha) increases the total ecosystem services value by 88% and 50% for the Mfolozi Floodplain and St Lucia System respectively. Results showed that economic values for existence, fisheries, tourism and water provision increase by the greatest percentage for the St Lucia System under both restoration scenarios. Partial and full restoration of the floodplain will result in the greatest increases in economic value for the services existence, tourism, fisheries and the harvesting of vegetation on the Mfolozi Floodplain.
Keywords: Lake ecology -- South Africa -- Saint Lucia, Lake; Ecology -- Economic aspects -- South Africa -- Kwazulu-Natal; Wetland ecology -- South Africa -- Kwazulu-Natal; Ecosystem services -- South Africa -- Kwazulu-Natal